Greasing the wheels of international commerce: how services facilitate firms' international sourcing - Peter Debaere; Holger Görg; Horst Raff (Verein für Socialpolitik, 2010)
We use unique plant-level data to study the link between the local availability of services and the decision of manufacturing firms to source materials from abroad. To guide our empirical analysis we develop a monopolistic-competition model of the materials sourcing decisions of heterogeneous firms. The model generates predictions about how the intensity of international sourcing of materials depends on a firm's productivity and the availability of local services. These predictions are supported by the data. We find evidence that more productive manufacturing firms tend to have a higher ratio of imported materials to sales. In addition, we find evidence that services grease the wheels of international commerce: A greater availability of services across regions, industries and time increases a firm's foreign sourcing of materials relative to sales. Interestingly, this positive impact of local service availability on imports especially applies to stand-alone firms that, unlike multinationals, are less likely to rely on imported or internally provided services.
Keywords: F12; L23; F10; 330; international trade; services; off-shoring; supply chain management; firm heterogeneity